Women Workers in the Second World War : Production and Patriarchy in Conflict. - Summerfield, Penny (Routledge library editions. Women's history., 2013)
The Second World War is often seen as a period of emancipation, because of the influx of women into paid work, and because the state took steps to relieve women of domestic work. This study challenges such a picture. The state approached the removal of women from the domestic sphere with extreme caution, in spite of the desperate need for women's labour in war work. Women's own preferences were frequently neglected or distorted in the search for a compromise between production and patriarchy. However, the enduring practices of paying women less and treating them as an inferior catego.